APPLICATION OF APR-01 M “MEDNORD PIEZOELECTRIC THROMBOPLASTOGRAPH IN PREGNANT WOMEN WITH HYPERTENSIVE DISORDERS - Muhamedova, Sh.S.; Tuxtabaeva, G.M.; Yusupbaev, R.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Determination with the method Thromboelastography of the global coagulation of pregnant women blood of with hypertensive disorders. Material and methods: We studied 40 pregnant women with hypertensive syndrome and aggravated obstetric history of hospitalization patients. The studies were conducted in the clinic of Republican Center of obstetrics and Gynecology of the Ministry of Health of the Republic of Uzbekistan. The state of the blood coagulation system was studied using an APR-01 M “MEDNORD” piezoelectric thromboelastograph (Russia). Results: Variations in the hemostatic potential depending on the trimester of pregnancy were revealed: in the first trimester, chronometric hypercoagulation is observed, in the second, chronometric hypocoagulation is observed, in the third - a hypercoagulative shift at the proteolytic stage, with chronometric hypocoagulation at the stages of polymerization and clot stabilization. Conclusions: With ARP-01M Mednord piezoelectric thromblastograph (PTEG), it is possible to determine 18 parameters of the hemostasis system at any time of the day without additional use of reagents.